Prediksi Kinerja Bundaran Tiga Lengan - Panji Septiana; Athaya Zhafirah; Greece Maria Lawalata (Institut Teknologi Garut, 2025)
This three-arm roundabout in a densely populated and traffic-rich area serves as a connecting provincial road that often experiences congestion. This study aims to evaluate the performance of the roundabout under existing conditions and projections for the next 10 years. The method used is quantitative through a three-week field survey on Sundays and Mondays at 07.00–17.00 WIB. The analysis refers to the 2023 Indonesian Road Capacity Guidelines (PKJI) to determine capacity, degree of saturation, delays, and queue opportunities. The results show that the current level of service is in category B with an average delay of 8 seconds/smp and a queue opportunity of 39–78%. In the 10-year projection, there has been a decrease in the level of service to category C with an average delay of 10 seconds/smp and a queue opportunity increasing to 97%. These results indicate that the roundabout will experience a decline in performance in the future, so it is necessary to consider geometric modifications or better traffic management to maintain smooth vehicle flow.